Digital Health Education for Tuberculosis Patients: A Systematic Review of Self-Care Improvement via Mobile Applications - Lismayanti, Lilis; Elengoe, Asita; Sansuwito, Tukimin; Falah, Miftahul (Journal of Advanced Research Design, 2025)
Tuberculosis (TB) remains a significant global health challenge, ranking among the leading causes of mortality worldwide. Indonesia, as of 2023, has the second-highest number of TB infections globally, according to WHO. This study evaluates the effectiveness of mobile applications in enhancing self-care, particularly treatment adherence among TB patients. A systematic review was conducted using four databases which are PubMed, Google Scholar, ProQuest, and Dimensions—to analyze studies published between 2019 and 2023. A total of 51 articles were screened, and 7 met the inclusion criteria. Findings highlight that digital health education via mobile applications significantly improves self-care and treatment adherence among TB patients, offering a practical alternative to direct observation therapy. The review underscores the importance of such tools in supporting daily treatment regimens. Future research should examine diverse application features, focusing on intervention feasibility and cost-effectiveness.